Ionothermal synthesis, structure, and bonding of the Catena-heteropolycation1∞ [Sb2Se2]+ - Groh, Matthias F.; Breternitz, Joachim; Ahmed, Ejaz; Isaeva, Anna; Efimova, Anastasia; Schmidt, Peer; Ruck, Michael (Zeitschrift für Anorganische und Allgemeine Chemie, 2015)
The reaction of antimony and selenium in the Lewis-acidic ionic liquid 1-butyl-3-methyl-imidazolium tetrachloridoaluminate, [BMIm]Cl•4.7AlCl3, yielded dark-red crystals of [Sb2Se2]AlCl4. The formation starts above 160 ° C; at about 190 ° C, irreversible decomposition takes place. The compound crystallizes in the triclinic space group P 1¯ with a = 919.39(2) pm, b = 1137.92(3) pm, c = 1152.30(3) pm, α = 68.047(1)° , β = 78.115(1)° , γ = 72.530(1)° , and Z = 4. The structure is similar to that of [Sb2Te2]AlCl4 but has only half the number of crystallographically independent atoms. Polycationic chains 1∞ [Sb2Se2]+ form a pseudo-hexagonal arrangement along [011¯] ], which is interlaced by tetrahedral AlCl4 - groups. The catena-heteropolycation 1∞ [Sb2Se2]+ is a sequence of three different four-membered [Sb2Se2 ] rings. The chemical bonding scheme, established from the topological analysis of the real-space bonding indicator ELI-D, includes significantly polar covalent bonding in four-member rings withinthepolycation.Theringsareconnectedintoaninfinitechainbyhomonuclear non-polar Sb-Sb bonds and highly polar Sb-Se bonds. Half of the selenium atoms are three-bonded.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Antimony; Chain structures; Heteropolycations; Main-group elements; Selenium